2021
DOI: 10.1016/j.sjbs.2021.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ocean acidification on the growth and biochemical composition of a green alga (Ulva fasciata) and its associated microbiota

Abstract: In marine ecosystems, fluctuations in surface-seawater carbon dioxide (CO 2 ), significantly influence the whole metabolism of marine algae, especially during the early stages of macroalgal development. In this study, the response of the green alga Ulva fasciata for elevating ocean acidification was investigated using four levels of p CO 2 ~ 280, 550, 750 and 1050 µatm. Maximum growth rate (6.6% day −1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 75 publications
2
9
0
Order By: Relevance
“…Characterization of optimized biomass shows high carbon, oxygen and phosphorus accumulation with resulted maximum absorption peaks in spectral region of carbohydrates and lipids. The carbohydrates content (58% (w/w) of CDW) of optimized biomass was found comparably higher than carbohydrates content of strains reported earlier such as Ulva fasciata (46.96%), Chlorella salina (50%) ( Barakat et al, 2021 , Mayers et al, 2018 ) and comparable with the highest carbohydrate content of 49% and 50% reported for commercially important microalgae Chlamydomonas sp . ( Morales-Sánchez et al, 2020 ) and Chlorella vulgaris ( Ferreira et al, 2019 ) respectively.…”
Section: Discussionsupporting
confidence: 43%
“…Characterization of optimized biomass shows high carbon, oxygen and phosphorus accumulation with resulted maximum absorption peaks in spectral region of carbohydrates and lipids. The carbohydrates content (58% (w/w) of CDW) of optimized biomass was found comparably higher than carbohydrates content of strains reported earlier such as Ulva fasciata (46.96%), Chlorella salina (50%) ( Barakat et al, 2021 , Mayers et al, 2018 ) and comparable with the highest carbohydrate content of 49% and 50% reported for commercially important microalgae Chlamydomonas sp . ( Morales-Sánchez et al, 2020 ) and Chlorella vulgaris ( Ferreira et al, 2019 ) respectively.…”
Section: Discussionsupporting
confidence: 43%
“…The Mediterranean Sea is home to around 1124 seaweed species, at least 20% of which are indigenous [ 34 , 35 ] and which are represented throughout the year. However, this area needs to be taken in our consideration, as it faces anthropogenic activity, ocean acidification [ 36 , 37 ], microplastic pollution [ 38 ], etc. According to the previous stress and pollution, these seaweeds accumulate several primary and secondary metabolites that can be used in several applications, such as carbohydrates, making them a good bioethanol source.…”
Section: Introductionmentioning
confidence: 99%
“…Protein content was determined according to the Bradford method [ 87 ]. Total carbohydrates were estimated by spectrophotometry using phenol–sulphuric acid against glucose standard [ 88 ] according the procedures of the previous studies [ 81 , 89 ].…”
Section: Methodsmentioning
confidence: 99%